Primary Care Physicians' Attitudes Toward Postpartum Depression - Saralee Glasser; Daphna Levinson; Rena Bina; Hanan Munitz; Ze'ev Horev; Giora Kaplan (SAGE Publishing, 2016)
Objectives: This study surveyed Israeli primary care physicians' attitudes and practice regarding postpartum depression (PPD). Methods: Participants included 224 pediatricians and family practitioners responding to an online survey (65% response rate). Results: Almost all respondents (98.0%) considered it important that they be able to recognize the signs of PPD. Most (89.8%) noted that if they suspected PPD, they would become somewhat involved: clarifying, keeping attentive, consulting with colleagues, and/or referring the woman to another professional. Six respondents-only family practitioners-stated that they would treat the case themselves ( P = .01). Family practitioners were significantly more willing to screen for PPD than were pediatricians (91.2% vs 64.6%; P < .0001). There were no differences between physicians by region or between males and females when comparing all respondents, as well as when comparing within medical specialty ( P < .05). Conclusions: There is a clear difference between considering the importance of recognizing signs of PPD and acting on it. Family practitioners had more favorable attitudes than did pediatricians, however screening in pediatric facilities is considered by many to be optimal. Hopefully future directions for medical education and health policy for family practitioners and pediatricians, as well as obstetrician/gynecologists, will meet the challenge of early identification and treatment of PPD for the benefit of women, infants and families.